Parents’ experiences of teacher outreach in the early years of schooling - Daniel, Graham R (My University, 2015)
Parent involvement in family–school partnerships is widely acknowledged as supporting children's schooling outcomes. This involvement, however, reduces as children move through the school grades, and can be lower in families from disadvantaged backgrounds. Teacher facilitation of parent involvement, or teacher outreach, is strongly linked to the establishment and maintenance of parental involvement in these partnerships. An understanding of teacher outreach is therefore necessary to inform the development of effective outreach practice in schools. Drawing on longitudinal data from a nationally representative sample, this research investigated parents' experiences of teacher outreach in the early years of formal schooling. Overall, perceived teacher outreach declined between Year 1 and Year 3. Families from low socio-economic backgrounds reported similar experiences of teacher outreach as families from other backgrounds. Families from Aboriginal and Torres Strait Islander backgrounds experienced lower levels of teacher outreach in both Year 1 and Year 3, and a greater reduction than other families between these years. Families from culturally and linguistically diverse backgrounds experienced lower levels of outreach in Year 1, but a similar level to parents from other backgrounds in Year 3. The implications of these findings for family–school partnership practice, professional learning and further research are considered.
Keywords: Education and Training -- Quality; Children -- School age; Education and Training -- Early Childhood; Learning, education and training; Education and Training; Children; School age; Quality; Early Childhood; Learning, education and training